Electrospun TiO2 nanofibers coated with polydopamine for enhanced sunlight‐driven photocatalytic degradation of cationic dyes. (1st October 2018) - Hou, Xuebin; Cai, Yibing; Song, Xiaofei; Wu, Yue; Zhang, Junhao; Wei, Qufu
Abstract : Controlled polydopamine (PDA)‐coated TiO2 composite nanofibers (NFs) were successfully fabricated via a facile electrospinning process and exposing TiO2 NFs into a slightly alkaline dopamine solution. Chemical composition, structural morphology, and photocatalytic degradation property of as‐prepared TiO2 NFs and PDA‐coated TiO2 composite NFs were characterized by Fourier transfer infrared, X‐ray photoelectron spectra, transmission electron microscopy, UV‐vis diffuse reflectance spectra, and photocatalytic degradation experiments. The results indicated that the core‐shell TiO2 @PDA composite NFs were successfully prepared and the thickness of PDA shell was highly controlled within several nanometers. And obtained TiO2 @PDA composite NFs exhibited improved photocatalytic performance after PDA coating, which is attributed to the photosensitization of PDA shell. Moreover, with increased pH values of initial solution, both absorption capacity in the dark and photocatalytic performance of TiO2 @PDA composite NFs showed significant improvement. Additionally, the obtained composite NFs showed different degrees of enhancement in photocatalytic performance based on different dyes, which is related to the "bait" effect of PDA shell. Comparing with anionic dyes, TiO2 @PDA composite NFs tended to adsorb and degrade more cationic dye molecules. It is anticipated that the fabricated composite NFs with controlled core‐shell structure have great potential to be applied for organic pollutants removal, especially cationic dyes.